Pişirici Cihaz Üretiminde Tesis İçi Su Geri Kazanımının Değerlendirilmesi - Gümüşlü, Efe (Fen Bilimleri Enstitüsü, 2016)
Endüstriyel faaliyetlerden kaynaklanan çevre kirliliğinin giderek artması ve doğal kaynakların tükenmeye başlaması nedeniyle işletmelerin çevreye karşı sorumlulukları da artmaktadır. Uluslararası anlaşmalar, yasal gereklilikler ve insanların çevre konusundaki artan duyarlılıkları nedeniyle işletmeler, hizmet ve üretim süreçlerinde çevreye duyarlı üretim ve hizmet tekniklerini benimsemeye başlamışlardır. Metal son işlem endüstrisi yüksek miktarlarda su kullanan endüstriler arasındadır. Bu sebeple atıksu arıtımı ve tekrar kullanımının geliştirilmesi, ekonomik ve çevresel sürdürülebilirlik açısından büyük önem taşımaktadır. Proseslerden oluşan atıksuları uygun artıma sistemleri uygulandığı takdirde geri kazanılabilir. Bu çalışmada incelenen işletme "Metal Son İşleme Tesisi" olup, üretim prosesi gelen metallerin şekillendirilmesi ve renklendirilmesinden sonra monte edilerek ürünün oluşturulması prensibine dayanmaktadır. Üretim prosesi için gerekli olan metal levhalar istenilen boy ve ölçülerde kesilmekte ve sonra üründe kullanılacağı bölgeye göre hatlara ayrılmaktadır. Bu aşamadan sonra metal levhalar üründe kullanılacakları yere göre emaye kaplamaya ya da boyama prosesine gönderilmektedir. Yapılan çalışmada metal son işlem endüstrisi kaynaklı atıksuyun arıtımdan geçirilerek proses içinde tekrar kullanımı sağlamak ve böylelikle su kullanımını minimum seviyelere indirmek amaçlanmıştır. Emaye kaplama ve boyama prosesi olmak üzere iki farklı prosesten kaynaklı atık sulardan numuneler toplanarak ayrı ayrı karakterizasyon çalışmaları yapılmış proseslerin kirlenme profilleri çıkarılmıştır. Elde edilen numunelerden diğer numune noktalarına göre en temizleri seçilmiş ve debileri oranında karıştırılarak her proses için birer kompozit numuneler elde edilmiştir. Bu kompozit numuneler üzerinde membran arıtım sistemleri uygulanmış ve sonuçları irdelenmiştir. Birinci bölümde çalışmanın önemi ve amacı hakkında bilgi verilerek çalışma kapsamı anlatılmıştır. İkinci bölümde ilgili endüstrinin kategorisinin tanımı yapılarak prosesler hakkında genel bilgiler verilmiş, endüstrinin çevresel etkileri irdelenmiştir. Üçüncü bölümde endüstride yapılan geri kazanım uygulamaları ve yaygın membran teknolojileri hakkında bilgi verilmiştir. Ayrıca literatürde bu endüstri ile ilgili yapılan çalışmalar değerlendirilmiştir. Dördüncü bölümde çalışmanın gerçekleştirildiği fabrika tanıtılarak prosesleri hakkında detaylı bilgiler ve uygulanan analiz yöntemleri verilmiştir. Beşinci bölümde proses ve kirlenme profilleri oluşturulmuş ve karakterizasyon çalışmaları gerçekleştirilmiştir. Altıncı bölümde seçilen akımlarla oluşturulan kompozit numunelerde geri kazanım uygulaması gerçekleştirilmiştir. Son bölümde ise genel olarak yapılan çalışmalar olumlu ve olumsuz yönleri ile değerlendirilip elde edilen bulgular neticesinde sonuçlar değerlendirilmiştir. Bu sonuçlar doğrultusunda da ileriye yönelik yaklaşımlar ve öneriler yapılmıştır.

When considered within the perspective of serious climate change we are facing, wastewater reclamation and reuse practices appear as not an option but a necessity. Industrial wastewater reuse is an inseparable part of sustainable production concept. Following agricultural, industrial sector is one of the largest users of water for development, consuming 5-10% of global water withdrawals. The OECD Environmental Outlook to 2050 predicts that global water demand for manufacturing will increase by 400% from 2000 to 2050 which is much larger than any other sector. Industrial wastewater reclamation and reuse practices covering the reuse of process wastewaters or others within the same facility for various water input requirements, as well as their applications in industrial parks are documented. A wide variety of cases dealing with industrial premises ranging from textile mills, pasta manufacturing, fish canning industries, breweries, display manufacturing, metal finishing etc. can be found in literature. Metal coating industry which is usually categorized under the metal finishing sector is one of the industries that consume high amount of water. Therefore, actions regarding the improvement of wastewater treatment and reuse should be undertaken on both economic and environmental sustainability grounds. Process wastewater can be reused for more purposes if the appropriate treatment systems are installed to treat the wastewater to the quality level required for reuse. Recent studies published in the literature revealed that membrane separation techniques may help in solving the problem of attaining a suitable quality of water that allows being recycled back to the process. The metal finishing factory where this study is conducted is one of the biggest white-goods manufacturers in Turkey. The sheet metal parts either manufactured in the mechanical production department or provided from other industries, are directed to surface pre-treatment processes namely, degreasing, rinsing, nano-ceramics coating and deionization rinsing process. These surface pre-treatment processes are applied consecutively. Metal sheets are encased in oil film in order to prevent the oxidation of metals during the enamel and painting processes. In the degreasing process the metal sheets are cleaned to increase the efficiency of coating process. In addition to degreasing process there are two wastewater generating processes in the industry namely enamel and painting processes. In the factory there are two enamel coating units called as Enamel Process Ankur and Enamel Process Imel both targeting to bring more thermal resistance to the product. There are no major differences between the two Enamel processes, but in case of necessity Enamel Imel supports Enamel Ankur. In the painting process, product parts which are exposed to 200°C temperatures are painted. Silver, white-black and anti-finger processes are the specific painting processes that are classified under the painting. Silver and white-black processes are named according to the colour of the paint, while anti-finger process is related to a paint speciality. The products of anti-finger process become stain proofed of fingerprints. The pieces that passed through surface pre-treatment are painted in powder coating process. In the facility, powder painting is performed by automatic paint guns. Since this is a dry process not generating any effluent, it is beyond the scope of this study. There exists also a styrofoam production unit where packaging materials are manufactured. Quite a high amount of wastewater, (26,500 m3/year) is generated from styrofoam production. The water requirements of paint, enamel and styrofoam processes are 83,744; 53,140 and 58,220 m3/year, respectively. The paint process has the highest water consumption. All the manufacturing processes are evaluated in terms of their wastewater reuse potential. To do so the results of a detailed segregated wastewater characterization are appraised by considering the process water quality requirements. Relatively clean segregated wastewater streams (reusable wastewaters) are separately collected. After stream segregation for reuse, the reusable wastewater generation capacity of paint and enamel processes are evaluated to be 146 and 109 m3/day, respectively. Although the most polluted composite wastewater is originated from the paint process, the reusable part of paint process wastewaters has the highest volume with less pollution loads among other processes. The parameters can easily be removed by membrane systems for this segregated effluent. As a result, application of membrane separation will be sufficient to obtain process water from segregated paint wastewaters. The reusable wastewater streams arising from paint process has a neutral pH around 7 so neutralization is not required. Paint composite sample is prepared by mixing wastewater discharges of Silver, White-black and Antifinger tagged with "SBS2","SBE3", "SBE4" and "SBA1". The reason of selecting those wastewater streams are having the highest flowrate (873.6 m3/week) and lowest pollutant concentrations. It should be noted that the selected streams have the minimum organic carbon concentration. The composite sample has approximately pH 7 and low organic matter content (
Evaluation Of Water Recovery At Cooking Device Manufacturing Plants
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Çevre Mühendisliği; Geri Kazanım; Atık Su; Arıtım; Sanayi; Metal Kaplama Endüstrisi; Environmental Engineering; Reuse; recycle; Wastewater; Treatment; Industry; Metal Finishing Industry